Strategic asset allocation of a reserves' portfolio: Hedging against shocks - Mario Torriani; Pablo Orazi; Matias Vicens (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2020)
Central bank reserves function as a liquidity buffer to mitigate country exposure and vulnerability to external shocks. Emerging Market Economies are the countries most exposed to the volatility of capital flows and have usually preferred to build up large war-chests of international reserves as a self-insurance mechanism, as it is under their full discretion. Nevertheless, the standard practice of immobilizing large amounts of "cash" to insure against jumps in volatility and riskaversion could be enhanced. The inclusion in the strategic asset allocation decision of external shocks' hedging strategies, which may increase the market value of the reserves' portfolio when reserves are more needed, can help to enhance the risk management of the national balance sheet. This paper presents a framework that seeks to enhance the strategic asset allocation of a central bank, by including in the portfolio construction the analysis of correlations between the reserves' portfolio and the country's main vulnerabilities to external shocks.
Keywords: 330; Zentralbank; Schock; Währungsreserven; Risikomanagement; Hedging; Lateinamerika